DESIGN, DEVELOPMENT AND IMPROVEMENT OF AN EMULGEL CONTAINING SILVER NANOPARTICLES AND VITAMIN D-3 FOR ITS POTENTIAL TO ACCELERATE THE HEALING OF WOUND - YADAV, RISHU; PANDEY, NARENDRA KUMAR; KUKKAR, RAJIV (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this research work was to prepare a topical emulgel based dosage form incorporated with vitamin D-3 and silver nanoparticles to reduce the wound healing time in any kind of wound. Methods: Central Composite Design (CCD) was applied for the optimization of emulgel by using Design expert software. Three responses (pH, viscosity, and in vitro drug release) and two factors (Carbopol concentration and stirring duration) were chosen, and Statistical Analysis of Variance (ANOVA) revealed that all the factors were significantly affecting the responses. Silver Nanoparticles (SNPs) was prepared with Green Tea Extract (GTE) and evaluated for particle size, Poly Dispersity Index (PDI), zeta potential and Fourier Transform Infra-red (FTIR) spectroscopy and revealed that SNPs of desired range and stability have been synthesized. Here excision wound model was used to evaluate the wound healing activity of formulation in vivo. Results: Maximum in vitro release 88.2±2.1 has shown by the optimized formulation F13, pH and viscosity were also found in optimum range i.e., 6.2±0.4 and 1672±33 respectively, followed by Korsmeyer and Peppas model. Total eight groups were designed for animal study and silver sulphadiazine was used as marketed formulation. F13 formulation was further evaluated for in vivo data, it was revealed that emulgel loaded with high dose of vitamin D-3 along with silver nanoparticles has shown 100.5±1.7% wound contraction, while marketed formulation has shown 103.7±1.1% wound contraction, which was much similar with test formulation. Cytotoxic cell study was done using assay on chicken egg, formulation has not shown any cytotoxic behaviour like haemolysis and cell damage on chick embryo’s blood vessels. Accelerated stability study of the optimized formulation was also performed to check whether the formulation was stable or not and it was revealed that optimized formulation was found stable for the period of six months. Conclusion: It was revealed that emulgel loaded with high dose of vitamin D-3 and SNPs found suitable to accelerate wound healing and showed almost similar response in wound contraction on comparison with marketed formulation. This emulgel promised to controlled the delivery of the drug for the longer duration.